Textbook of fish diseases - Conroy, D. A. (T. F. H., 1970)
The present book attempts to be something of usefulness, as well as being easy to handle and to understand, not only to the specialist who is occupied full - time with the study of fish biology, buy also for the veterinarian and others who may be interested in the breeding of crap. trout, and ornamental aquarium fishes, and for aqurists and fishermen.